8 Patients' perspectives of living with epilepsy or psychogenic non-epileptic seizures: a thematic analysis investigating patients' writings. Issue 8 (13th July 2017) - Rawlings, Gregg H; Brown, Ian; Stone, Brendan; Reuber, Markus
Abstract : Objective: This study examines the subjective experience of living with epilepsy or psychogenic non-epileptic seizures (PNES) by qualitatively analysing patients' written accounts. Qualitative methodologies can produce fine grained and rich detail, as patients are able to describe, in their own words, what is important to them. Writing is an individual act allowing for private exploration and expression, and has previously been used to reveal insights into the phenomenology of other conditions. Method: Patients were recruited from a United Kingdom hospital and from membership-led organisations for individuals living with seizures. This dataset was collected in the context of a randomised control trial investigating a writing intervention for patients with seizures. The current data was captured by asking patients to handwrite or type: about their very deepest thoughts and feelings about their condition; a letter to their condition; a letter to their younger self; and about a personal value and why it is important to them. Patients were asked to write for at least 20 min per question, at home, in private and on separate days. Questions were used to guide patients towards reflecting on their experiences of living with seizures. The four questions were adapted from the literature investigating writing therapies for clinical populations. All the writings were analysed thematically using a theory and data driven approach. Results: Patients with epilepsy (n=20) and PNES (n=19) were matched on sample size, age, gender, education, quality of life, seizure severity, and words written. In the writings of patients with epilepsy, five key-themes and 22 sub-themes emerged from the data. The five themes reflected experiences of seizure onset, seizure symptoms, treatment and outcome, living with epilepsy, and displays of coping. In patients with PNES, six key-themes and 29 sub-themes emerged. The six themes reflected accounts of: aetiology and development, seizure symptoms, emotions, living with PNES, lack of understanding by themselves, others, and healthcare professionals, and treatment and outcome. Conclusion: Thematic differences were observed between the two conditions. Patients with PNES regularly described their symptoms and how people have reacted to their condition, especially themselves and healthcare professionals. Patients with epilepsy focused on how the condition has affected their lives, in which, they portray themselves as coping and 'fighting' to live a 'normal' life. The findings from this study add to the growing research applying qualitative methodologies to investigate the phenomenology of epilepsy and PNES. Understanding patients' experiences can hold diagnostic, treatment and prognostic implications.